Incidence and predictors of pericardial effusion following surgical closure of atrial septal defect in children: A single center experience - Martina Campisano; Camilla Celani; Alessio Franceschini; Denise Pires Marafon; Silvia Federici; Gianluca Brancaccio; Lorenzo Galletti; Fabrizio De Benedetti; Marcello Chinali; Antonella Insalaco (Frontiers Media S.A., 2022)
ObjectivesTo evaluate the incidence of pericardial effusion (PE) after surgical atrial septal defect (ASD) closure and to investigate the presence of predictive risk factors for its development.MethodsWe collected data from 203 patients followed at Bambino Gesù Children's Hospital of Rome who underwent cardiac surgery for ASD repair between January 2015 and September 2019.ResultsA total of 200/203 patients with different types of ASD were included. Patients were divided into two groups: Group 1) 38 (19%) who developed PE and Group 2) 162 (81%) without PE. No differences were noted between the two groups with regard to gender or age at the surgery. Fever in the 48 h after surgery was significantly more frequent in group 1 than in group 2 (23.7 vs. 2.5%; p < 0.0001). ECG at discharge showed significant ST-segment elevation in children who developed PE, 24.3 vs. 2.0% in those who did not (p < 0.0001). Group 1 patients were divided into two subgroups on the basis of the severity of PE, namely, 31 (81.6%) with mild and 7 (18.4%) with moderate/severe PE. Patients with moderate/severe PE had a significantly higher BMI value (median 19.1 Kg/m2) (range 15.9-23.4, p = 0.004).ConclusionThe presence of fever and ST-segment elevation after surgery predicts subsequent development of PE suggesting a closer follow-up for these categories of patients. A higher BMI appears to be associated with a higher risk of moderate/severe PE.